Analysis of Individual and Organizational Factors on Nurses' Perception in Reporting Patient Safety Incidents - Dewi Fadilatul; Indasah Indasah; Agusta Dian Ellina (Indonesian Journal of Global Health Research, 2025)
Patient safety is a situation where patients are protected from all risks of injury that should not occur during health services, one effort is by reporting incidents. The aim of this research is to analyze individual and organizational factors regarding nurses' perceptions in reporting patient safety incidents. Quantitative research method survey method with a cross sectional approach. Samples were collected using purposive sampling technique, totaling 243 respondents. The data collection technique uses a questionnaire. Validity is tested using Pearson’s correlation, with items valid if the coefficient exceeds the critical r-value at 5% significance. Reliability is assessed with Cronbach’s Alpha, where a coefficient above 0.600 indicates acceptable consistency. The data analysis technique uses multiple linear regression. The research results show that the factors that have an influence on nurses' perceptions are motivation indicators, reward/punishment and hospital policy, this is because the sig value. < 0.05. Meanwhile, the indicators that have no effect are the knowledge, training and leadership indicators, this is because the sig value. > 0.05. It was concluded that individual and organizational factors, namely indicators of motivation, reward/punishment and hospital policy, had an influence on nurses' perceptions, while the results that had no influence were indicators of knowledge, training and leadership